PERANCANGAN SISTEM INFORMASI PRESENSI GURU BERBASIS WEB PADA SD MASEHI PAYETI 2 - Ina, Novantri Tamu; Pekuwali, Arini Aha (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
This study examines the importance of Information Technology implementation in schools to support teaching, learning, and administrative activities, focusing on the development of a Teacher Attendance Information System at Masehi Payeti 2 Elementary School. Currently, attendance is conducted manually, with teachers recording names and signing an attendance book, a method prone to being unstructured and susceptible to errors, data damage, and delays. To address these issues, this study aims to develop a web-based application that allows attendance to be conducted more effectively, efficiently, and managed in real time. The application is built using the Waterfall method with PHP, HTML, and MySQL programming languages. Based on usability testing using the System Usability Scale (SUS) with five respondents, the application received an average score of 70.5, which falls into the "Marginal High" category with a grade scale of C and an adjective rating of "OK." This score indicates a fairly positive user perception of the system's usability, suggesting that it is comfortable and efficient for teachers to use. This study's findings are expected to improve discipline and the accuracy of attendance data at Masehi Payeti 2 Elementary School, while also contributing to the adoption of more modern information systems within school environments.